El procedimiento de solicitud de adecuación de los datos de conformidad con la identidad de género. Reflexiones desde el derecho fundamental a la protección de datos (Tema Central) - Ordóñez Pineda, Luis (2019)
Nowadays, the fundamental right to the protection of personal data is considered as an institution guaranteeing other fundamental rights. Moreover, with respect to Advisory Opinion OC-24/17 of the Inter-American Court of Human Rights, the right to gender identity shares with this fundamental right a series of principles and guarantees that, from the constitutional point of view, strengthen respect of the equality and non-discrimination. Under these considerations, this article tries to highlight the importance of establishing accountability and pertinent measures that guarantee that the procedure for requesting the adaptation of the data in accordance with the gender identity corresponds to the protection of sensitive or specially protected data.